Attention Deficit Hyperactivity Disorder (ADHD) and Young People in NSW Custody - John Kasinathan; Joey Le (Bond Law Review)
Attention deficit hyperactivity disorder (ADHD) is a disorder characterised by inattention, hyperactivity and impulsiveness, which can negatively impact learning and development and have lifelong implications. ADHD is more prevalent in marginalised groups, including young offenders. International and Australian evidence has more recently increased understanding about the variety of mental health problems that affect young offenders, including ADHD. However, exploration of ADHD in young offenders, cannot be divorced from an increasing understanding that young offenders have high rates of mental illness generally, with a high level of comorbidity. Young offenders further evince high rates of re-offending, re-incarceration and premature mortality. This expert commentary explores a preliminary examination of ADHD and psychiatric disorder comorbidity as elucidated by the Young People in Custody Health Survey (YPiCHS) conducted in NSW in 2015. A description of the current state of physical and mental health service provision to young people interacting with the criminal justice system in NSW is provided. Improving our understanding of ADHD youth and comorbid psychiatric disorders in detention may help inform prevention, intervention, policy and practice.